2019
DOI: 10.1042/cs20180600
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 activation induced by neutrophil extracellular traps sustains inflammatory response in the diabetic wound

Abstract: Persistent inflammatory response in the diabetic wound impairs the healing process, resulting in significant morbidity and mortality. Mounting evidence indicate that the activation of Nod-like receptor protein (NLRP) 3 inflammasome in macrophages (MΦ) contributes to the sustained inflammatory response and impaired wound healing associated with diabetes. However, the main trigger of NLRP3 inflammasome in the wounds is not known. Neutrophils, as sentinels of the innate immune system and key stimulators of MΦ, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(111 citation statements)
references
References 60 publications
3
96
0
Order By: Relevance
“…Moreover, DNase I also promoted the transition of M1 to M2 macrophage phenotype, which improved the clearance of inflammatory products and thereby the healing rate of corneal wound in diabetic mice. Similarly, previous study had confirmed that DNase I promoted wound repair in diabetic rats by alleviating the activation of NLRP3 inflammasome, 44 suggesting that DNase I can not only reduce the inflammatory response of neutrophils, but also that of macrophages.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Moreover, DNase I also promoted the transition of M1 to M2 macrophage phenotype, which improved the clearance of inflammatory products and thereby the healing rate of corneal wound in diabetic mice. Similarly, previous study had confirmed that DNase I promoted wound repair in diabetic rats by alleviating the activation of NLRP3 inflammasome, 44 suggesting that DNase I can not only reduce the inflammatory response of neutrophils, but also that of macrophages.…”
Section: Discussionmentioning
confidence: 55%
“…As a characteristic of inflammation resolution, the transition impairment of M1 to M2 macrophage phenotype was involved in the impaired wound healing in diabetic condition 44‐46 . Immunofluorescence staining results showed the enhanced staining of anti‐F4/80 (a macrophage marker) and anti‐CD206 (a M2 macrophage marker) in diabetic cornea, whereas topical application of DNase I remarkably reduced the infiltration of M1 macrophages and increased the proportion of M2 macrophages in diabetic cornea at 48 hours after injury (Figure 3A).…”
Section: Resultsmentioning
confidence: 97%
“…It has also been suggested that NETs could promote vessel occlusion by providing a scaffold for platelets, RBCs and pro-coagulant molecules (48). Recent studies also demonstrated that NETs induced the activation of the NLRP3 inflammasome in macrophages through TLR4/TLR9 signaling pathways, leading to higher production of IL-1β in the context of diabetes and atherosclerosis (49,50). Indeed, one may suspect a role of NETs in SCD pathogenesis through an activation of the immune innate system (15).…”
Section: Hemolysis Neutrophil Extracellular Traps (Nets) and Inflammentioning
confidence: 99%
“…TLRs are one of the pattern recognition receptors involved in innate immunity, a class of important protein molecules that link natural immunity with specific immunity. TLR2 and TLR4, as members of the TLRs family, play an important role in inflammation, bacterial infection, and autoimmune diseases [23]. The regulation of VEGF expression can improve the microvascular lesions in diabetes, resulting in insufficient local blood perfusion, and thus regulates the progression of diabetic foot disease [24].…”
Section: Discussionmentioning
confidence: 99%